Orthopaedic Resident Preparation and Confidence in Treating On-Field Injuries. Issue 5 (31st May 2017) - Hodax, Jonathan D.; Sobel, Andrew D.; DeFroda, Steven; Chambers, Alison B.; Hulstyn, Michael J.
Background: Orthopaedic surgery residents may cover athletic events, although the training provided to prepare residents for this role and oversight from attending physicians during these activities is not well understood. Purpose: To survey orthopaedic residents about the training provided by their residency program for on-field athletic coverage and to understand their levels of preparation for this role and confidence in treating commonly encountered on-field conditions. Study Design: Descriptive epidemiology study. Methods: An anonymous survey was emailed to residents in all American College of Graduate Medical Education–accredited, allopathic, nonmilitary orthopaedic surgery residency programs. This survey queried residents about their demographics, the opportunities their residencies require or allow for athletic coverage, their level of preparation for serving an on-field physician, and their comfort level with treating a number of on-field conditions. Likert-type scales were used to assess resident comfort level for treating 13 orthopaedic and nonorthopaedic conditions as well as their perceived level of preparedness. Results: Of 148 residency programs contacted, 57 programs responded (39%). Of the 57 programs responding, 51 (89.5%) allowed or required residents to cover athletic events, and 27 of 51 (52.9%) reported that training to prepare for this role was provided. Only 6 of 24 programs without training available (25%) had direct attending supervision of residents at all athletic events. Residents who answered that their residency programs mandate training prior to their participation in athletic coverage activities reported a higher level of preparation for this role than those with no training, optional training, or those who were unsure of their training requirement ( P < .0001, P = .035, and P = .013, respectively). In addition, the more senior the resident was, the higher the level of confidence was in treating all orthopaedic and some nonorthopaedic conditions. Residents who had mandatory training displayed a higher comfort level in treating on-field orthopaedic and nonorthopaedic conditions than those without training. Conclusion: Formal training of orthopaedic residents prior to their covering athletic events can improve confidence in treating orthopaedic and nonorthopaedic conditions. Many programs do not ensure that residents are familiar with key and potentially life-saving equipment. An opportunity exists to improve resident education.